Worldwide Cultural Impact on World Cup: Changing Cultural Dynamics in Indonesia - Rachmawati, Iin (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
World Cup 2022, just like any other World Cup parties, are changing the cultural dynamics in Indonesia. That World Cup event is not only changing cultural dynamics in football, but also in music, festival, fashion, cuisine, and lifestyle. During the World Cup event which had been held from November 20th to December 18th 2022, it can be clearly found in the mass media that every single media had discussed a lot about Qatar World Cup 2022. And everyone, including K-Pop fans were talking about the World Cup event since the opening ceremony. This phenomenon was not only happened in Qatar, but also in every country around the world including in Indonesia. Thus, based on that phenomenon, this research explored more about worldwide cultural impact on World Cup 2022 in changing cultural dynamics in Indonesia and how it is related to the fans’ cultural conceptualizations. Qualitative content analysis method had been used to explain more about the details on cultural dynamic changing and its relation to the fans’ cultural conceptualizations. Kashima’s theory about the mechanism of cultural dynamics and Sharifian’s theory about cultural conceptualizations used in this research. The end result showed that World Cup can be such a great media for uniting people from various different cultural backgrounds to gather around and minimize their cultural differences. For more, media has played such a great role to fully support those dynamic cultural changing in Indonesia. Also, in international context, those football fans may not share the same system of cultural conceptualizations although they use the same language to engage in communication with each other. And Korean wave has great influence in changing cultural dynamic as well as adding more cultural information.